2013
DOI: 10.1128/jvi.01095-13
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Aptamers That Bind to Geminivirus Replication Proteins Confer a Resistance Phenotype to Tomato Yellow Leaf Curl Virus and Tomato Mottle Virus Infection in Tomato

Abstract: Geminiviruses constitute a large family of single-stranded DNA viruses that cause serious losses in important crops worldwide. They often exist in disease complexes and have high recombination and mutation rates, allowing them to adapt rapidly to new hosts and environments. Thus, an effective resistance strategy must be general in character and able to target multiple viruses. The geminivirus replication protein (Rep) is a good target for broad-based disease control because it is highly conserved and required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 87 publications
0
79
0
Order By: Relevance
“…In Nigeria, moderate resistance in four pepper cultivars has been identified [79]. In addition to the conventional breeding, different transgenic approaches for achieving resistance or tolerance have been tested against begomoviruses infecting tomato and pepper [80][81][82] and this may be a way forward for obtaining durable resistance. In West and Central Africa, leaf curl disease is regarded as the most important biotic stress for okra, and there is a lack of viral resistance/tolerance [58,83].…”
Section: Resistancementioning
confidence: 99%
“…In Nigeria, moderate resistance in four pepper cultivars has been identified [79]. In addition to the conventional breeding, different transgenic approaches for achieving resistance or tolerance have been tested against begomoviruses infecting tomato and pepper [80][81][82] and this may be a way forward for obtaining durable resistance. In West and Central Africa, leaf curl disease is regarded as the most important biotic stress for okra, and there is a lack of viral resistance/tolerance [58,83].…”
Section: Resistancementioning
confidence: 99%
“…Similar study was also performed in TYLCV and Tomato mottle virus infection, in which peptide aptamers interacting with Rep proteins were targeted. This study also revealed that two of the peptide aptamers interacted with the Rep proteins from viruses representing three major Geminiviridae genera, providing broad spectrum resistance [26].…”
Section: Peptide Aptamers Mediated Resistance Against Geminivirusesmentioning
confidence: 96%
“…Peptide aptamers are small peptides, usually no longer than 20 amino acids, that interfere with protein interactions. Transgenic tomato lines expressing aptamers selected from a library of random sequences by repeated screening were shown to exhibit no or very mild symptoms upon infection with either TYLCV or ToMoV and to contain lower levels of viral DNA (Reyes et al, 2013).…”
Section: Other Control Strategiesmentioning
confidence: 99%